APLIKASI INVENTORY ALAT TULIS KANTOR PADA KANTOR KECAMATAN WATUKUMPUL KABUPATEN PEMALANG - Humam, Muhammad; Afriliana, Ida (Politeknik Harapan Bersama, 2016)
The development of information technology at the moment is very rapidly so that humans in doingany work always need a computer to support the performance in meeting the need for speed and accuracyof the data. As well as the data processing inventory of stationery, which supplies a stationery will beorganized properly using appropriate computer system. At the District Office Watukumpul, inventory ofoffice stationery was not well-organized, namely supplies of stationery still use a little note in everytransaction. Therefore, it needs adequate application in the inventory system so that a more optimal andwell-organized.The measures used in this study was a needs analysis, system design and system testing.The method used in this application system design by using UML (Unified Modeling Language) anddatabase design using MySQL. As for the collection of data using the method of observation, interviewsand literature. As for the software using Microsoft Visual Basic 6.0.Applications office stationeryinventory is expected to assist staff in organizing and optimizing data reporting office stationery at theDistrict Office Watukumpul Pemalang.Keywords: inventory, stationery, Microsoft Visual Basic 6.0